Developing a Local Wisdom-Based Mind Mapping Enrichment Book for Poetry Writing in Grade IV Elementary School - Rinjani, M. Pd., Ersila Devy Rinjani; Feni; Nur Rois; Haekal Adha Al-Giffari (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to develop a poetry writing enrichment book using a mind mapping model integrated with local wisdom to enhance the learning experience of fourth-grade students at MI Kawengen 01 Ungaran Timur, Semarang Regency. The research employed the 4-D development model (Define, Design, Develop, and Disseminate) involving needs analysis, product design, expert validation, and user response testing. Data were collected through questionnaires, expert evaluations, and user feedback from both teachers and students. The findings revealed that both teachers and students expressed strong needs for poetry learning materials that are simple, structured, and contextually relevant to students’ cultural environment. The developed product was validated by experts, with results showing 90% feasibility from design experts and 98.6% from material experts, indicating that the book is highly suitable for use. Furthermore, user responses were highly positive, with 95% approval from teachers and 89.2% from students, suggesting that the enrichment book is practical, engaging, and supportive of students’ creative writing development. The study concludes that combining mind mapping with local wisdom not only enhances cognitive scaffolding but also fosters cultural literacy, making the enrichment book both pedagogically effective and contextually meaningful for primary education.